Is time a significant factor in the release of potassium from lithium heparin plasma and serum? - Petersmann, Astrid; Ceglarek, Uta; Gauß, Karen Friederike; März, Winfried; Meyer, Alexander von; Nauck, Matthias (Clinical chemistry and laboratory medicine, 2025)
Der Artikel Is time a significant factor in the release of potassium from lithium heparin plasma and serum? wurde am 1. Oktober 2025 in der Zeitschrift Clinical Chemistry and Laboratory Medicine (CCLM) (Band 63, Heft 11) veröffentlicht.
Gesehen am 21.11.2025